Experiences and Perspective of Caretakers Working in Childcare Institutes in Delhi: A Qualitative Inquiry - Prerna Sharma; Yashika Sharma (Indian Journal of Social Psychiatry, 2025)
Context: Institutional care is a common alternative for children who have been displaced from their homes due to a variety of socioeconomic factors. The quality of care and well-being of children in such institutions has been under research due to its long-lasting impacts on a child’s early development. However, the perspective of caregivers who are an important point of contact with the children is yet to be explored thoroughly. Aim: The current study aims to understand the experiences of caregivers in childcare institutes (CCIs) through a qualitative lens of inquiry. Settings and Design: The study has employed a qualitative, exploratory, inductive research design. Methodology: A semi-structured focus group discussion (FGD) schedule was developed, and FGDs were held with caregivers across seven CCIs in five districts of New Delhi. Qualitative Analysis: Using analysis software (QSR NVIVO 10), thematic analysis was conducted in two stages, namely, initial coding and focused coding to organize the data into meaningful themes. Results: The thematic analysis revealed a set of 4 main themes, 13 subthemes, and more than 200 codes emerging from the qualitative dataset. The themes threw light on key challenges and concerns that caretakers of children in institutional care often face. The caretakers’ current knowledge of psychological concerns and the gap in providing psychologically informed care for children is emphasized. Conclusion: The study highlights some key beliefs, such as stigma regarding mental health concerns and perceptions about their work as a “duty.” In addition, knowledge among caregivers about specific psychological issues such as self-harm and aggression may influence caring for children. Furthermore, prominent skillset challenges such as the management of children with emotional and behavioral concerns, and children with disability were highlighted. The findings reveal that the caregivers experience workplace burden due to a lack of adequate resources and specialized knowledge in childcare.